Development of biopolymer composites using lignin: A sustainable technology for fostering a green transition in the construction sector - Barney H. Miao; Robert J. Headrick; Zhiye Li; Leonardo Spanu; David J. Loftus; Michael D. Lepech (Cleaner Materials)
Developing sustainable construction materials is important to help reduce the anthropogenic impacts of the construction industry. Currently, the production of concrete accounts for 8 % of global carbon emissions. Therefore, alternatives to concrete must be developed, to reduce its use in the future. New construction materials will help to facilitate a green transition as envisioned in global climate initiatives. Materials such as lignin are ideal, as they can be implemented with little additional cost to manufacture construction materials. We introduce a novel material, lignin-based biopolymer-bound soil composite (BSC), which is similar to other BSCs using other types of biopolymers. In addition, a design methodology is presented, which allows the manufacture of lignin-based BSCs with tailored characteristics. Two kinds of lignin — hydrolysis lignin and alkali lignin — were investigated, with five mix designs developed for each type of lignin. The lignin-based BSCs were found to have compressive strength ranging from 1.6–8.1 MPa, which allows them to be implemented in non-structural construction applications. Ultimate compressive strength, density, and other parameters were measured, leading to the development of design relationships for lignin-based BSC. The design relationships presented in this study will help introduce lignin-based BSC as a sustainable form of construction.